The combined effects of silicon dioxide nanoparticles and cold air exposure on the metabolism and inflammatory responses in white adipocytes. Issue 5 (25th July 2017) - Zhang, Yongqiang; Li, Xi; Lin, Yangsheng; Zhang, Li; Guo, Zhan; Zhao, Dandan; Yang, Danfeng
Graphical Abstract: Abstract: The potential hazard of nanoparticles (NPs) from air pollution has attracted widespread attention. Though the toxicology of NPs has been intensively studied, few works have been reported on the combined effect of silicon dioxide (SiO2 ) NPs and cold air exposure at the cellular level. Herein, we evaluated the combined effect of SiO2 NPs and cold exposure on metabolism and the inflammatory responses in white adipocytes by qRT-PCR in vitro . After SiO2 NP or cold exposure, there were significant changes in the expressions of adipogenic genes and proinflammatory cytokine genes in white adipocytes. The mRNA levels of IL-6, IL-8, TNF-α and IL-1β were upregulated by SiO2 NP or cold exposure, and more so in the combined group. The expressions of the proinflammatory cytokine genes IL-6, IL-8, TNF-α and IL-1β increased highly significantly ( P < 0.01) in the SiO2 NP alone group and the combined group, compared with the control. The expressions of the cold group tended to be upregulated significantly compared with the control in IL-6 ( P < 0.01) and IL-8 ( P < 0.05). The results demonstrated that there was antagonistic effect between SiO2 NPs and cold air on the plasticity and metabolism in white adipocytes, where the main effect of cold air on the plasticity and metabolism was significant ( P < 0.05). However, there was a synergistic effect between SiO2 NPs and cold air on the toxic effects in white adipocytes, in which the main effect of SiO2 NPs on the toxic effects was significant ( P < 0.05). In conclusion, SiO2 NPs combined with cold exposure induced a stronger inflammatory response and influenced the plasticity and metabolism in white adipocytes, accompanied by more serious health hazards.